Supplementing day-old pigs with bovine colostrum or milk replacer - Bandyk, C.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seventy-five litters of newborn pigs from gilts were given either 20 cc of bovine colostrum or 20 cc of milk replacer through a stomach tube, and their weaning weight, scouring, and survival were compared with those of newborn pigs that were not treated. Results were broken down by birth weight groups: small-less than 2.3 lb.; medium-2.3 to 2.9 lbs.; large-3.0 lbs. and over. No significant differences in weaning weights were observed from treatment. Nontreated pigs tended to scour more than pigs treated with bovine colostrum but this difference was not statistically significant, partly because of the variation in the incidence of scouring in the farrowing groups. Overall, the most severe scouring occurred from days 9 to 14 after birth. Survival rates increased within each treatment with increasing birth weight. Survival rate by treatment was 91.05% for colostrum-treated, 89.11% for milk replacer treated and 88.32% for nontreated pigs; thus, the colostrum-treated pigs had 2.8% lower death loss than control pigs. This improvement in survival rate was similar for each weight group.
Keywords: Swine; Bovine colostrum; Milk replacer